Cystic Adventitial Disease of the Common Femoral Artery: A Rare-Case Report - Wang, Qilong; Cheng, Zhihua; Tang, Liang; Wang, Qi; Zhang, Ping; Zhang, Hua (Frontiers in Surgery, 2022)
Herein, we report the case of a 59-year-old man with intermittent claudication of 100 m, who complained of resting pain in his lower right extremity. A pelvic, contrast-enhanced, computed tomography scan showed the presence of cystic density in the lower segment of the right common femoral artery. Faced with the risk of acute limb ischemia, we navigated a challenging diagnostic procedure to choose an appropriate treatment for him. Additionally, we performed a pathological investigation of the excised common femoral artery following the excision bypass. On postoperative day 5, the patient was discharged from the hospital. During the 2-year follow-up, no new cysts were discovered, and the patient had favorable prognosis.